Recent Progress in NIR-II Contrast Agent for Biological Imaging - Cao, Jie; Zhu, Binling; Zheng, Kefang; He, Songguo; Meng, Liang; Song, Jibin; Yang, Huanghao (Frontiers in Bioengineering and Biotechnology, 2020)
Fluorescence imaging technology has gradually become a new and promising tool for in vivo visualization detection. Because it can provide real-time sub-cellular resolution imaging results, it can be widely used in the field of biological detection and medical detection and treatment. However, due to the limited imaging depth (1-2 mm) and self-fluorescence background of tissue emitted in the visible region (400-700 nm), it fails to reveal biological complexity in deep tissues. The traditional near infrared wavelength (NIR-I, 700-950 nm) is considered as the first biological window, because it reduces the NIR absorption and scattering from blood and water in organisms. NIR fluorescence bioimaging’s penetration is larger than that of visible light. In fact, NIR-I fluorescence bioimaging is still interfered by tissue autofluorescence (background noise), and the existence of photon scattering, which limits the depth of tissue penetration. Recent experimental and simulation results show that the signal-to-noise ratio (SNR) of bioimaging can be significantly improved at the second region near infrared (NIR-II, 1000-1700 nm), also known as the second biological window. NIR-II bioimaging is able to explore deep-tissues information in the range of centimeter, and to obtain micron-level resolution at the millimeter depth, which surpass the performance of NIR-I fluorescence imaging. The key of fluorescence bioimaging is to achieve highly selective imaging thanks to the functional/targeting contrast agent (probe). However, the progress of NIR-II probes is very limited. To date, there only are few reports about NIR-II fluorescence probes, such as carbon nanotubes, Ag2S quantum dots and organic small molecular dyes. In this paper, we surveyed the development of NIR-II imaging contrast agents and their application in cancer imaging, medical detection, vascular bioimaging and cancer diagnosis. In addition, the hotspots and challenges of NIR-II bioimaging are discussed. It is expected that our findings will lay a foundation for further theoretical research and practical application of NIR-II bioimaging, as well as the inspiration of new ideas in this field.